Molecular typing of Kell, Kidd, and Duffy antigens in direct antiglobulin test-positive autoimmune hemolytic anemia patients - Atul Sonker; Anju Dubey; Yatendra Mohan (Asian Journal of Transfusion Science)
BACKGROUND: In autoimmune hemolytic anemia (AIHA) patients, conventional pretransfusion testing is difficult to interpret due to the presence of autoantibodies which may show panreactivity. Molecular phenotyping of red cell antigens could potentially be used to precisely match blood units, thereby reducing the need to perform intensive serologic laboratory testing, hence time delay in providing transfusion to such patients. The aim of this study is to perform the molecular typing for Kell, Kidd, and Duffy blood group antigens in direct antiglobulin test (DAT)-positive red blood cells of AIHA patients and provide corresponding antigen-matched blood for transfusion therapy. MATERIALS AND METHODS: Blood samples from 50 normal blood donors and 30 DAT-positive AIHA patients were tested using standard serological techniques and polymerase chain reaction-based methods for Kell (K/k), Kidd (Jka/Jkb), and Duffy (Fya/Fyb) blood group systems. Five patients requiring blood transfusion were given donor blood units identical for Kell, Kidd, and Duffy antigens and followed up. RESULTS: Genotyping and phenotyping results were 100% concordant for normal blood donors. Serological phenotyping of minor red cell antigens showed varied degree of agglutination for AIHA patients. The molecular typing was able to detect the antigen frequency accurately in all samples. The results of genotyping were used to provide Kell-, Kidd-, and Duffy-matched blood for transfusion therapy to AIHA patients with no adverse reaction. CONCLUSION: Molecular blood group typing has proved immensely useful in the determination of actual antigen profile and hence in providing appropriate transfusion support in patients with AIHA reduced risk of transfusion reactions and alloimmunization.